2020
DOI: 10.1093/jat/bkaa185
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Metals in Liquid and Aerosol from Pod-Type Electronic Cigarettes

Abstract: High-quality, accurate data on liquid contents and aerosol emissions from electronic nicotine delivery systems (ENDS, e.g., e-cigarettes) are crucial to address potential health concerns as these devices evolve and mature. Metals are an important class of ENDS constituents that merit attention as they have various health implications. Proper sampling, handling and aerosol trapping materials are essential to generate accurate quantitative metal data and to reduce the likelihood of inaccurate results originating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 19 publications
6
42
1
Order By: Relevance
“…The wires connecting the heating block to the battery were composed of Ni and Cr and the holder was primarily composed of Ni. These materials in this cannabinoid delivery system were similar to those previously reported for nicotine delivery systems, although nickel was more prevalent than copper and brass [ 7 , 8 , 9 ].…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…The wires connecting the heating block to the battery were composed of Ni and Cr and the holder was primarily composed of Ni. These materials in this cannabinoid delivery system were similar to those previously reported for nicotine delivery systems, although nickel was more prevalent than copper and brass [ 7 , 8 , 9 ].…”
Section: Resultssupporting
confidence: 79%
“…Because available sample volume only permitted one analytical replicate, results that were slightly above our reportable level, could not be repeated. It should be noted that method LODs reported for this study were slightly higher than reported in a previous study [ 9 ] as a result of the analysis of only 15 puffs of aerosol due to limited availability of sample volume and possibly due to the additional tube rinse with an organic solvent.…”
Section: Resultscontrasting
confidence: 63%
See 3 more Smart Citations